Quotation of Proudhon, with date and address, Paris ...., grand rue, 10, 30 avril 1863" under photo. Donation of Boris Souvarine in 1983 - Bourson, F.
Quotation of Proudhon, with date and address, Paris ...., grand rue, 10, 30 avril 1863" under photo. Donation of Boris Souvarine in 1983.